Achievement goals and self-determined motivation in Botswana elite youth athletes: An extension of achievement goals and self-determination theories - Mabuta, K. D.; Hill, C. R.; Male, L. (African Journal for Physical, Health Education, Recreation and Dance, 2021)
This study examined whether data from an elite African youth sport context support the tenets of the Self-Determination Theory (SDT) and if the youths` achievement goals were associated with their self-determined motivation. Eighty-two male (n =37) and female (n = 45) national athletes from Botswana aged 13-18 years old (M = 16.46, SD = 1.40) who participated in the African Youth Games completed the revised Sport Motivation Scale (SMS-II) and the Perception of Success Questionnaire. A confirmatory factor analysis (CFA) of the SMS-II showed that data from Botswana support the relative autonomy continuum postulated by the SDT. A multiple regression analysis showed task-orientation to be a significant ( ß= .25, p = .04) predictor of relative autonomy, while ego-orientation was not. The study offers support to existing findings on the relationship between SDT and achievement goal orientations and presents a valuable perspective from a less studied sport context. Enhancing task-orientation in competitive youth sport may be a pathway to the development of self-determined motivation.